UPAYA MENINGKATKAN KETERAMPILAN BERBICARA MELALUI CERITA BERGAMBAR PADA KELAS I DI SD NEGERI 2 METRO BARAT TAHUN AJARAN 2010/2011 - marsini marsini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
The background of this research is the low activity of learning and speaking skills of students, its approximately about 3 to 4 students (15% to 21%), and the speech was halting, inaccurate and not coherent. Moreover, with the result of reflection and consultation with colleagues eventually we concluded that the need to immediately look for alternative solutions in an effort to develop and improve the ability to speak another language skill. This research is a classroom action research conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. Data collection techniques used by observation, documentation, and testing. The collected data was then analyzed using qualitative and quantitative analysis. The results showed that the students were able to pronounce vocabulary through picture books, children who reach the percentage is very high gain values ​​from 0% to 11% the first cycle and the second cycle reaches the percentage of very high gain values ​​from 0% to 78%, could tell the story with pictures provided, children who reached a very high percentage of getting value from 0% to 83%, retelling the stories that have been told, a child who reaches a very high percentage of getting value from 05 to 5.5% the first cycle to the second cycle reaches a very high percentage gain value from 0% to 67% Keywords: Activity learning, speaking skills